On Norm Estimates for Derivations in Norm-Attainable Classes - Nyabonyi, J. Z.; Okelo, N. B.; Obogi, R. K. (Eur. J. Math. Anal, 2023)
In this note, we provide detailed characterization of operators in terms of norm-attainability and norm estimates in Banach algebras. In particular, we establish the necessary and suﬃcient conditions for norm-attainability of the derivations and also give their norm bounds in the norm attainable classes.
Keywords: Norm Estimates